The family hope program using AHP method - Aminudin, Nur; Huda, Miftachul; Suhaila Ihwani, Siti; Shakib Mohd Noor, Sulaiman; Basiron, Bushrah; Azmi Jasmi, Kamarul; Safar, Jimaain; Kilani Mohamed, Ahmad; Hassan Wan Embong, Wan; Marzuki Mohamad, Ahmad; Maseleno, Andino; Masrur, M.; et al. (International Journal of Engineering and Technology, 2018)
The Government program in tackling the economic crisis that has occurred so far is by providing direct assistance to very poor families (KSM) in every village throughout Indonesia. The Family Hope Program (FHP) is one of the government's conditional aid programs as a form of compensation from the fuel price increase, which certainly affects the lives of the wider community, including the poor. In order for the expected results to be more accurate and the system designed is arranged systematically, the authors decided to use Analytical Hierarchy Process (AHP). This decision support model will describe the problem of multi-factor or multi-criteria into a form of hierarchy, From the results of the test the shrill and weight of FHP assistance is the type of work of the head of the family is not fixed in the first rank with 4.9 shrill. With the results of the output is feasible or not prospective recipient in FHP, obtained from the comparison of the lamda weight of the rating category with the weight value of the predetermined ratio.Â Â